ANALISA KADAR AMONIA DAN UJI LOGAM BERAT (Fe dan Mn) PADA AIR LIMBAH DOMESTIK - Tentriati Cahaya; Aman Sentosa Panggabean; Moh Syaiful Arif (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
A study entitled Analysis of Ammonia Levels and Heavy Metals (Fe and Mn) in Domestic Wastewater has been conducted. This research aimed to determine the concentrations of ammonia and heavy metals (Fe and Mn) in domestic wastewater from the drainage channel on Jalan H. M. Ardans (AL 1) and the wastewater treatment plant of PT. LAB (AL 2). Ammonia levels were analyzed using the phenate spectrophotometric method, while heavy metal concentrations (Fe and Mn) were determined using the Atomic Absorption Spectrophotometry (AAS) method. Based on the analysis results, ammonia levels were found to be 0.45 mg/L in AL 1 and 0.08 mg/L in AL 2. The concentration of iron (Fe) was 3.17 mg/L in AL 1 and 0.50 mg/L in AL 2. The concentration of manganese (Mn) was 15.07 mg/L in AL 1 and 0.30 mg/L in AL 2. The ammonia levels in both AL 1 and AL 2 complied with the quality standard of 10 mg/L. The Fe concentrations in AL 1 and AL 2 also met the quality standard of 5 mg/L. The Mn level in AL 2 met the quality standard of 2 mg/L, whereas the Mn level in AL 1 exceeded the permissible limit. Keywords: ammonia, iron (Fe), domestic wastewater, manganese (Mn)